2021
DOI: 10.1371/journal.pone.0257060
|View full text |Cite
|
Sign up to set email alerts
|

Association of the functionally significant polymorphisms of the MMP9 gene with H. pylori-positive gastric ulcer in the Caucasian population of Central Russia

Abstract: Background and purpose The study analyzed the association of functionally significant polymorphisms of matrix metalloproteinases (MMPs) genes with the development of gastric ulcer (GU) in Caucasians from Central Russia. Methods The 781 participants, including 434 patients with GU (196 Helicobacter pylori (H. pylori)-positive and 238 H. pylori-negative) and 347 controls (all H. pylori-negative) were recruited for the study. Ten SNPs of the MMP1 (rs1799750), MMP2 (rs243865), MMP3 (rs679620), MMP8 (rs1940475), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
3
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 76 publications
(99 reference statements)
3
3
0
4
Order By: Relevance
“…It was also possible to determine the genotypic and allelic frequencies of the three MMP SNPs, with high rate of successful genotyping and within the HWE. All minor allele frequencies were in accordance with previous studies [ 18 , 36 , 37 , 38 , 39 , 40 , 41 ]. The MMP-9 rs17576G allele frequency is 30.1% in the Chinese population (N = 1007) [ 40 ], 37.1% in the Romanian population (N = 197) [ 39 ], 21% in the Egyptian population (N = 100) [ 37 ], 36.1% in the Russian population (N = 347) [ 41 ] and 36.2% in the Slovenian population (N = 161) [ 38 ].…”
Section: Discussionsupporting
confidence: 89%
“…It was also possible to determine the genotypic and allelic frequencies of the three MMP SNPs, with high rate of successful genotyping and within the HWE. All minor allele frequencies were in accordance with previous studies [ 18 , 36 , 37 , 38 , 39 , 40 , 41 ]. The MMP-9 rs17576G allele frequency is 30.1% in the Chinese population (N = 1007) [ 40 ], 37.1% in the Romanian population (N = 197) [ 39 ], 21% in the Egyptian population (N = 100) [ 37 ], 36.1% in the Russian population (N = 347) [ 41 ] and 36.2% in the Slovenian population (N = 161) [ 38 ].…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies have demonstrated the role of the 2G*rs1799750 MMP1 allele as a risk factor for both POAG, 1315,17,20 PACG, 15,17 and exfoliation glaucoma. 17,27 According to our data, this allele is also associated with an earlier age of disease manifestation. However, we did not find a relationship between this locus and the risk of POAG in Caucasians from Central Russia.…”
Section: Discussionsupporting
confidence: 67%
“…26 Eight loci of the three MMP genes: MMP1 (rs1799750), MMP3 (rs679620), and MMP9 (rs3918249, rs17577, rs17576, rs3787268, rs2250889, rs3918242), were chosen. For MMP loci selection, the following criteria were applied 27,28 : 1) previously reported associations with glaucoma (POAG, etc. ), 2) epigenetic (regulatory) potential, 3) SNP minor allele frequency (MAF) > 0.05.…”
Section: Deoxyribonucleic Acid (Dna) Extraction Snps Selection and Ge...mentioning
confidence: 99%
“…To estimate the potential downstream functional effects of the AD-associated variants and their proxies (r 2 ≥0.8) [ 46 , 47 ], we used the available data of epigenetic effects (HaploReg [ 34 ]), non-synonymous functional predictions (SIFT and PolyPhen-2 databases [ 48 , 49 ]), expression and alternative splicing quantitative traits (GTExconsortium atlas, [ 50 ]). HaploReg and European population data of the 1000 Genomes Project Phase 1 were used to identify variants in close linkage disequilibrium (r 2 ≥ 0.8) with the AD-associated variants [ 51 , 52 ].…”
Section: Methodsmentioning
confidence: 99%